Design and Experiment Research of Accelerated Fatigue Life Tester for Plastic Gear - Zhaoyao Shi; Wei Wang; Bo Yu; Ping Li; Dong Xin (Jixie chuandong)
Based on the principle of constant stress accelerated fatigue life test，a testing machine for plastic gears is developed to test the fatigue life quickly. The working principle，structure composition and the design of core parts of the testing machine are mainly studied. On the whole，the horizontal structure is adopted，the special gear tooling is designed to ensure the test accuracy，and the temperature control box is used to adjust and control the test environment temperature. The experimental device can accurately measure the influence of speed，torque，temperature and cycle times of plastic gear on transmission efficiency. The experimental results show that the higher the torque is，the smaller the average efficiency，the higher the average temperature and the smaller the number of cycles are. It provides an efficient and feasible method and device for the life prediction and failure form research of plastic gear，which has theoretical value and practical application value.